Konsep Wayfinding untuk Perancangan Arsitektur Kesehatan Mental - Yosivan Erlanda Sutantio; Asri Dinapradipta; Arina Hayati (Universitas Sebelas Maret Surakarta, 2022)
Architectural design through the concept of wayfinding for mental health facilities can support the patient's healing process, by providing designs that can influence cognitive behavior. The main problem is how to solve the spatial disorientation in the building. The healing architecture theories observe and harness the environmental elements as a factor in the design of a building. This information is applied to help the occupants in the process identifying their environment. The statement provides a basis for ideas of ideas regarding the architecture that provides information on the occupant, and it presents a hypothesis about architecture as a guide the user inside the building (wayfinding). The design proposal aims is to produce proposed structures designed as facilities to deal with mental health disorders according to the needs of the patient, and knowing what architectural elements can be used in using the concept of wayfinding as a result of research.